ASSESSMENT OF THE SAFETY OF ULTRASOUND-GUIDED PERCUTANEOUS NEPHROLITHOTRIPSY (World Bulletin of Public Health, 2025)
The study aimed to assess the effectiveness and outcomes of ultrasound-guided percutaneous nephrolithotripsy (PCNLT) in treating patients with large renal pelvic stones. The analysis included 138 patients who underwent PCNLT for kidney stones between 2018 and 2024. Among them, 70 patients (Group 1) underwent the procedure under combined ultrasound and radiologic guidance, while 68 patients (Group 2) were operated on using ultrasound guidance alone. Patients with large pelvic stones larger than 2.2 cm requiring a single puncture access were included in the study. The comparative analysis evaluated operative time, number of intra- and postoperative complications, blood loss and hospitalization time. Percutaneous access was successfully performed in all patients. Postoperative complications (exacerbation of chronic pyelonephritis, macrohematuria) were observed in 14.3% of patients in group 1 and 14.7% in group 2. There was no bleeding requiring blood transfusion and injuries of neighboring organs. The efficacy of PCNLT in Group 1 was 95.7%, additional interventions were used in 3 (4.3%) patients. In group 2 the efficacy of PCNLT was 94,1%, 4 (5,9%) patients underwent additional remote lithotripsy. There were no significant differences in PCNLT efficacy, blood loss volume and hospitalization time. In case of large stones of the pelvis and sufficient expansion of the renal cavity system PCNLT can be performed under ultrasound control, which allows to reduce the radiation load on the patient and medical personnel.
Keywords: ultrasound control; requiring blood; pyelonephritis